Antiscience, Vaccine Hesitancy, and Pandemic Responses: Highlights from the Asia Pacific Summit on Infectious Diseases and Immunization - Ananta Seth; Nick Sevdalis; Zulkifli Ismail; Sri Rezeki Hadinegoro; Heidi J. Larson; Tikki Pangestu (Vaccines)
The recent resurgence of mpox highlights the urgent need for rethinking vaccination strategies globally, underscored by the painful memories of past public health crises where delayed responses and inequitable vaccine distribution exacerbated the spread of infectious diseases. The inaugural APIC-ADVA Asia Pacific Summit on Infectious Diseases and Immunization, themed “Vaccination for All: Access, Confidence and Equity (ACE)”, was held in Singapore from 31 October to 1 November 2023 in an attempt to present best practices and hard-won insights from battling COVID-19 and other pandemics in the Asia-Pacific region. This summit was co-convened by the Asia-Pacific Immunization Coalition (APIC) and Asia Dengue Voice and Action (ADVA). Local, regional, and international experts from academia, research and representatives from the Ministries of Health, the World Health Organization (WHO), and the International Vaccine Institute (IVI) participated in the 2 day summit. With more than 230 speakers and delegates from over 15 countries, and 4 symposia over 2 full days, the first APIC-ADVA Asia Pacific Summit on Infectious Diseases and Immunization highlighted critical issues affecting vaccine access, confidence, and equity, and emphasized the importance of safeguarding the world from existing infections and future pandemics through immunization.